2015
DOI: 10.1103/physreva.92.012321
|View full text |Cite
|
Sign up to set email alerts
|

Communication between general-relativistic observers without a shared reference frame

Abstract: We show how to reliably encode quantum information and send it between two arbitrary generalrelativistic observers without a shared reference frame. Information stored in a quantum field will inevitably be destroyed by an unknown Bogolyubov transformation relating the observers. However certain quantum correlations between different, independent fields will be preserved, no matter what transformation is applied. We show how to efficiently use these correlations in communication between arbitrary observers.-Int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Our framework can readily be applied to quantum information protocols in which the effect of acceleration or gravity cannot be ignored. As a future line of research, we are interested in employing our framework to study the effect of acceleration on communication between two relativistic observers without a shared reference frame [28,29] as well as continuous variable teleportation [30,31]. We are also interested in investigating analogous effects in other types of quantum fields such as massless (that cannot be obtained by taking m → 0 limit of the results of this paper; see footnote 1 in Sec.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Our framework can readily be applied to quantum information protocols in which the effect of acceleration or gravity cannot be ignored. As a future line of research, we are interested in employing our framework to study the effect of acceleration on communication between two relativistic observers without a shared reference frame [28,29] as well as continuous variable teleportation [30,31]. We are also interested in investigating analogous effects in other types of quantum fields such as massless (that cannot be obtained by taking m → 0 limit of the results of this paper; see footnote 1 in Sec.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…And for this reason, quantum correlations in fact intrinsically relevant to the foundational core of thermodynamics and information loss problem of black holes. On the other hand, the influence of gravity on quantum systems cannot be ignored with the advance in theory and technology of quantum information processing. For example, it has been experimentally demonstrated that the gravitational effects of the Earth notably influence the precision of atomic clocks for a variation of 0.33 m in height .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, relativistic quantum information [20][21][22][23][24][25][26][27][28][29][30][31][32][33], the study of quantum information processes and concepts in a relativistic setting, has been a blooming area of research for both conceptual and experimental reasons. Understanding quantum phenomena in a relativistic framework is necessary because the realistic quantum systems are essentially nonin-ertial.…”
Section: Introductionmentioning
confidence: 99%